Rumen degradable nitrogen supplement requirement for nutrient utilization from finger millet (Eleucine coracana) straw by crossbred cattle - PRASAD, C S; SAMPATH, K T; SHIVARAMAIAH, M T; SHIVAKUMAR, N; SUBBA RAO, A (The Indian Journal of Animal Sciences, 2013)
Finger millet straw (Eleucine coracana) supplemented with groundnut-cake (GNC) and cotton seed-cake (CSC) at 15 and 30 g level of rumen degradable nitrogen (RDN) per kg digestible organic matter (DDM) was fed to 30 crossbred heifers distributed equally under each regimen. The dry-matter intake of straw (DMIS) did not differ significantly under the 2 cake sources and nitrogen levels than that under the unsupplemented straw grouP. But the total DMI was significantly higher (p<0.05) under all the cake supplemented groups. However, the OM and NDF digestibility was significantly higher(p<0.05) in the groups receiving GNC at both levels (15 and 30 g RDN/kg DOM) than CSC supplemenlations as compared to unsupplemented group suggesting that for improved nutrient utilzation GNC was a better N-source than esc with finger millet straw (FMS). In another experiment when GNC and esc were supplemented at 15 g RDN/kg DOM level to heifers with ad lib. FMS no significant effect either on dry-maller or organic-matter intake of straw was observed. GNC was a better degradable N supplement.